Monocyte migration assay using a vascular-on-a-chip model and its utilization for the evaluation of a heated tobacco product - Hayashida, Ayaka; Nozawa, Atsuko; Ito, Shigeaki (Frontiers in Toxicology, 2025)
The use of Heated Tobacco Products (HTPs) is expected to have a reduced-risk potential for cardiovascular disease, including atherosclerosis, compared with combustible cigarettes (CCs) Because of the complex relationship between atherosclerosis and lifestyle factors, such as diet, physical activity, and smoking, focusing on the pathogenesis of atherosclerosis will help deepen our understanding of the reduced risk potential of HTPs. Organ-on-a-chip platforms are widely used to mimic human pathophysiology when studying such pathologic manifestations. In this study, a Vascular-on-a-Chip (VoC) model was used to mimic the characteristic physiology of the human vasculature and to establish an assessment model to measure three endpoints: endothelial barrier impairment, monocyte adhesion, and monocyte migration through vascular endothelial cells (VECs) which are the important initial key events in atherosclerosis. Macrophages were exposed to test cigarette smoke (CS) and HTP aerosol extracts, and conditioned medium was collected. VECs cultured on VoC were exposed to these conditioned media to mimic the effects on the vascular system caused by inflammatory responses elicited by inhaled substances. The HTP aerosol-exposed group had significantly reduced endothelial barrier impairment, monocyte adhesion, and monocyte migration compared with the CS-exposed group, and there was no significant difference with the solvent control. In summary, our model provided valuable insights into the reduced risk potential of an HTP compared with a CC by evaluating a series of endpoints in the early stage of atherosclerosis.